Durable drag reduction and anti-corrosion for liquid flows inside lubricant-infused aluminum/copper capillaries - Yan, Huilong (2022)
Frictional drag reduction and anti-corrosion for the liquid flows in micro- and nanochannels result in considerable economic and environmental benefits. The lubricant infused surface (LIS) has emerged as a promising technology for achieving the two functionalities. This work proposes the fabrication of LISs on the inner walls of metal capillaries for endowing the capillaries with sustainable drag reduction and anti-corrosion properties. Specifically, we demonstrate the fabrication of the LIS aluminum (Al) capillaries with varying viscosity of lubricants and systematically investigate their drag reduction performance by measuring the relationship between the frictional factor/slip length and Reynolds number. We find that the LIS Al capillary exhibits durable drag reduction and anti-corrosion characteristics which can also be achievable in other LIS metal capillaries, such as LIS copper capillaries. A comparison of the LIS Al capillary with the Al capillary with a superhydrophobic surface (SHS) suggests that the former outperforms the latter in terms of durability, e.g., the LIS capillary with the lowest lubricant viscosity considered can withstand a shear force as high as Re≈700, which is more than twice that of the SHS capillary (Re≈300). The LIS capillaries can reduce the frictional factor by up to 30%. Varying the viscosity of infusion lubricants is an effective way to tune the drag reduction performance of the LIS metal capillaries. The present work paves a way for applying LIS metal capillaries in instrumentation, thermal management, microfluidic devices, etc.